Estimating the Speed of rotation of a rotating X-Ray window (Global Journal of Science Frontier Research, 1969)
A rotating membrane is assumed to be a rotating disc and appropriate speed of rotation is a key consideration if the material in question must survive the heat flux imparted on it by impinging beam of electrons. 1Î¼m hot spots are assumed to be distributed on the target material such that a circular pattern is formed according to figure 1 .